Maternal mortality by socio-demographic characteristics and cause of death in South Africa: 2007-2015 - Nolunkcwe J. Bomela (BMC, 2020)
Abstract Background South Africa's maternal mortality ratio remains high although it has substantially declined in the past few years. Numerous studies undertaken in South Africa on maternal mortality have not paid much attention to how the causes are distributed in different socio-demographic groups. This study assesses and analyses the causes of maternal mortality according to sociodemographic factors in South Africa. Methods The causes of maternal deaths were assessed with respect to age, province, place of death, occupation, education and marital status. Data were obtained from the vital registration database of Statistics South Africa. About 14,892 maternal deaths of women from 9 to 55 years of age were analysed using frequency tables, cross-tabulations and logistic regression. Maternal mortality ratio (MMR), by year, age group, and province for the years 2007-2015 was calculated. Results The 2007-2015 MMR was 139.3 deaths per 100,000 live births (10,687,687 total live births). The year 2009 had the highest MMR during this period. Specific province MMR for three triennia (2007-2009; 2010-2012; 2013-2015) shows that the Free State province had the highest MMR (297.9/100000 live births; 214.6/100000 live births; 159/100000 live births) throughout this period. MMR increased with age. Although the contribution of the direct causes of death (10603) was more than double the contribution of indirect causes (4289) maternal mortality showed a steady decline during this period. Conclusions The study shows evidence of variations in the causes of death among different socio-demographic subgroups. These variations indicate that more attention has to be given to the role played by socio-demographic factors in maternal mortality.